Stage financing and syndication in the IPO underpricing of venture-backed firms: Venture capital and IPO underpricing. (November 2019) - Honorine, Awounou-N'dri; Emmanuelle, Dubocage
The article investigates the impact of stage financing and syndication practices on the underpricing level of venture-backed firms (VBFs) undertaking their initial public offerings (IPOs). This empirical study uses a unique hand-collected data set concerning more than 260 VBFs that went public on Euronext Paris and Alternext between 1997 and 2013. Our findings suggest a lower level of underpricing for firms backed by syndicated venture capital investment. Additionally, we find that the syndicate size is negatively associated with the level of underpricing. However, there is no evidence that stage financing has a significant impact. Syndication thus appears to be the only relevant mechanism to improve IPO performance (measured by the underpricing level), as it reduces agency costs and information asymmetry between the different stakeholders in an IPO process.